The Venetian Vernacular Lexicon in Eleventh‐ and Twelfth‐Century Latin Documents: Insights from the Codice Diplomatico Veneziano. - Gesiot, Jacopo (Transactions of the Philological Society, 2026)
This study investigates the lexicographical potential of Medieval Latin documentation from the Venetian area of the Italo‐Romance domain, highlighting the need for a systematic approach to bridge Latin and vernacular linguistic developments. The project MEDITA – Medieval Latin Documentation and Digital Italo‐Romance Lexicography. Integrated Resources for the New Historical and Etymological Lexicography has contributed to this field by cataloguing lexical forms and recovering geographically localized attestations, shedding light on non‐literary Medieval Latin, particularly in material and everyday contexts. The analysis also examines how emerging vernacular lexemes adapted to Latin scripta, considering formulaic language, lexical class, semantic context and pragmatic factors. Special attention is given to the distinction between proper and common nouns and the diachronic evolution of key lexical items. By addressing these aspects, the study enhances our understanding of the early presence and integration of Romance vocabulary in medieval documentary sources.